2018
DOI: 10.21608/ejnf.2018.75381
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Concentrate to Roughage Ratio on Nutrient Digestibility, Rumen Fermentation, Growth Performance and Serum Acute Phase Protein in Growing Buffalo Calves

Abstract: his study was accomplished to designed to assess the appropriate concentrate: roughage ratio (C:R) ratio for better nutrient digestibility, rumen fermentation patterns, healthy and economic beef production in Egyptian buffalo calves. Sixteen buffalo calves aged about 18-20 months of 292.5±4.7 kg average body weight were randomly assigned into four groups of 4 animals each. The treatment diets were composed of four concentrate: roughage (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Despite that, in this trial, an improvement of buffaloes' growth performance was observed in the groups fed on the diets characterized by high energy values and a lower forage/concentrate ratio. This result is in agreement with those of Abdel Raheem et al [37], who compared four different diets characterized by F:C ratios of 80:20, 75:25, 60:40, and 55:45. These authors found an increase in dry matter intake, daily weight gain, and final body weight by increasing the concentrate percentage in the diet.…”
Section: Discussionsupporting
confidence: 93%
“…Despite that, in this trial, an improvement of buffaloes' growth performance was observed in the groups fed on the diets characterized by high energy values and a lower forage/concentrate ratio. This result is in agreement with those of Abdel Raheem et al [37], who compared four different diets characterized by F:C ratios of 80:20, 75:25, 60:40, and 55:45. These authors found an increase in dry matter intake, daily weight gain, and final body weight by increasing the concentrate percentage in the diet.…”
Section: Discussionsupporting
confidence: 93%